2011
DOI: 10.1080/09658211.2011.590506
|View full text |Cite
|
Sign up to set email alerts
|

Memory for actions in autism spectrum disorder

Abstract: This study explored how memory for actions in children with autism spectrum disorder (ASD) and typically developing children might benefit from self-performance and experimenter demonstration, and whether these groups possess metamemory knowledge of their performance levels in this task. Children with autism were less accurate on the action memory task when they carried out each action themselves during encoding, or when no actions were implemented during this phase, but this difference was abolished when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
82
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 60 publications
8
82
2
Order By: Relevance
“…As such, in our view, it is not possible to draw any meaningful conclusions from this study. In a more recent study Wojcik et al (2011) also failed to find significant enactment effects among children with ASD. In contrast, on the same task typically developing children showed a clear enactment effect.…”
mentioning
confidence: 97%
“…As such, in our view, it is not possible to draw any meaningful conclusions from this study. In a more recent study Wojcik et al (2011) also failed to find significant enactment effects among children with ASD. In contrast, on the same task typically developing children showed a clear enactment effect.…”
mentioning
confidence: 97%
“…It is important to note that neither the study by Wilkinson et al (2010) nor the study by Wojcik et al (2011) assessed metacognitive control in ASD. To our knowledge, the only study ever to have assessed monitoring and control in ASD was by Sawyer et al (2014), who employed a JOC task that assessed both abilities in adults with ASD.…”
Section: Metacognition Mindreading and Autism Spectrum Disordermentioning
confidence: 99%
“…To date, only three studies have assessed JOC accuracy among individuals with ASD and these studies report mixed results (Sawyer, Williamson, & Young, 2013;Wilkinson, Best, Minshew, & Strauss, 2010;Wojcik, Allen, Brown, & Souchay, 2011). In Wilkinson et al (2010;Exp.…”
Section: Metacognition Mindreading and Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst self-concept inevitably plays a role in enhancing encoding, it has also been suggested that a self-enactment effect results from the additional motoric component of self-performed actions leading to more salient memory traces (Engelkamp & Zimmer, 1985, 1989. Given the motor difficulties (e.g., Ming, Brimacombe & Wagner, 2007) coupled with diminished self-awareness in ASD (see Lind & Bowler, 2010), it may come as little surprise that a number of researchers have reported a diminished or absent self-enactment effect in ASD (e.g., Dunphy-Leli & Wellman, 2012;Farrant, Blades & Boucher, 1998;Hare, Mellor & Azmi, 2007;Millward et al, 2000;Russell & Jarrold, 1999;Wojcik, Allen, Brown & Souchay, 2011). Russell and Jarrold (1999), for example, asked children with ASD, children with moderate learning difficulties (to act as IQ matches for the ASD group) and typically developing children to remember whether they or the experimenter had placed a picture card on a grid, either on their own behalf or on behalf of a doll partner.…”
mentioning
confidence: 99%